Probiotic effect of Bacillus subtilis B-2998D, B-3057D, and Bacillus licheniformis B-2999D complex on sheep and lambs - Devyatkin, Vladimir; Mishurov, Alexey; Kolodina, Evgenia (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: Probiotics are well documented for their health benefits by developing a balanced intestinal microbiota and boosting immunity. The present study was conducted to determine the effects of a probiotic preparation EnzimsporinTM (consisting of spore-forming bacteria Bacillus subtilis B-2998D, B-3057D, and Bacillus licheniformis B-2999D) on the biochemical, hematological, immunological parameters, intestinal microbiota, and growth dynamics of sheep and lambs. Materials and methods: Enzimsporin was fed to lambs and sheep at different doses to determine the bacteria’s probiotic effects. Sheep were divided into three groups (six each), which received 0, 1, and 3 gm of Enzimsporin/per head/day, respectively, and two groups of lambs (10 each), who received 0 gm and 1 gm of Enzimsporin/per head/day for 30 days in addition to their regular ration. On day 30, blood samples were collected, followed by the determination of biochemical, hematological, and natural resistance indicators. Fecal samples were examined to determine the intestinal microflora, and animals were weighed daily to determine their growth dynamics. Results: Supplementation of probiotics (EnzimsporinTM) improved the lambs’ body weight gain by 18.8%. Analysis of the clinical parameters showed improvements in the levels of total protein, globulins, and urea by 5.3%, 10.8%, and 6.2%, respectively, in the blood of probiotic-supplemented lambs. Similarly, an increment in the total protein, albumins, and globulins was observed in the sheep with EnzimsporinTM supplementation. The decrease in bilirubin and cholesterol levels in the blood and increased bactericidal and phagocytic index in the sheep and lambs with probiotic supplementation indicated a positive influence of EnzimsporinTM on the liver function and natural resistance. Furthermore, an increase in Lactobacillus and Bifidobacterium and a decrease in the Escherichia coli, Enterococcus, and Yeast in the fecal contents of experimental sheep and lambs indicated the potentiality of EnzimsporinTM on maintaining good gut health. Conclusion: Spore-forming bacteria B. subtilis B-2998D, B-3057D, and B. licheniformis B-2999D can be used in feeding sheep and lambs of 2 months of age to increase body weight gain, improve intestinal microbiota, strengthen the immune system, and maintain normal metabolic processes. J. Adv. Vet. Anim. Res., 8(1): 146-157, Mar 2021 http://doi.org/10.5455/javar.2021.h497